2004
DOI: 10.1109/lpt.2003.820470
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Experimental Study of Intrachannel Nonlinear Timing Jitter in a 10-Gb/s Terrestrial WDM Return-To-Zero System

Abstract: Abstract-Using a recirculating loop, we measured nonlinearly induced timing jitter in a terrestrial wavelength-division-multiplexed system at different transmission distances with different amounts of precompensation. Within each 600-GHz subband, we achieved error-free transmission using the same amount of precompensation for all channels at all distances up to 5000 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…With regards to the arrangement of dispersion compensation, it has been shown in [8] that the optimal precompensation should result in an accumulated dispersion function which is symmetric with respect to a 180 rotation about the transmission midpoint. Here, we have demonstrated that this analysis extends to installed systems; as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the arrangement of dispersion compensation, it has been shown in [8] that the optimal precompensation should result in an accumulated dispersion function which is symmetric with respect to a 180 rotation about the transmission midpoint. Here, we have demonstrated that this analysis extends to installed systems; as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used a digital sampling oscilloscope (DSO) with a 40-GHz bandwidth optical detection module to record the received eye diagrams, from which we extracted the signal timing jitter. In order to isolate the timing jitter that results from transmission, the inherent jitter of the oscilloscope, found in back-to-back measurements to be 1.1 ps, was deconvolved from the results [8]. We also used the DSO eye diagram to calculate the signal -factor, from the means and standard deviations of the marks and spaces measured at an ideal sampling point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, we show eye diagrams for a system similar to an experimental loop in our laboratory that we are using to emulate a long-haul terrestrial system with four channels spaced 200 GHz apart. 6 The main nonlinear effects in this system are intrachannel pulse-to-pulse interactions that result in bit-pattern-dependent timing shifts and distortions of the pulses. The eye diagram in Fig.…”
Section: Herementioning
confidence: 99%
“…The Q-factor as a function of the degree of polarization of the noise for a back-to-back system. The red curve shows the result obtained using Eq (6). and the circles show the experimental result when the Jones vectors of the signal and the polarized part of the noise are orthogonal.…”
mentioning
confidence: 99%